Indole-3-carbinol (I3C) as Leukemia Therapeutic Agents: Review - Karimabad, Mojgan N.; Mohamadi, Maryam; Torabizadeh, Seyedeh Atekeh; Hassanshahi, Gholamhossein (Mini Reviews in Medicinal Chemistry, 2023)
Leukemia or blood cancer was initially discovered in 1845 and this malignancy was reported in patients who had an amplified number of blood cells, in particular, White Blood Cells (WBC), due to this disease. The event of leukemia was further identified as a malignant hematopoietic disorder due to both uncontrolled and unlimited proliferation in combination with a lack of differentiation of the leukemic stem cells. Furthermore, 75 to 80% of the global population use herbal remedies as primary therapy, mainly because of their better efficiency and satisfaction, which elevate the human body symmetry with the minimum unwanted adverse effects. For the control of cancer, plant products, and fruits have been considered promising tools and are being consumed for centuries. Several plant extracts are also being used for the therapy and prevention of different types of known cancers. Indole-3-carbinol (I3C) is a natural material obtained from Brassica diversity of vegetables and has been reported to serve as a promising cancer preventative agent. In the present review, the authors mainly tried to focus on and emphasize I3C applications in leukemia treatment.
Keywords: vegetable